2021
DOI: 10.1177/07356331211025108
|View full text |Cite
|
Sign up to set email alerts
|

Online Self-Regulated Learning and Achievement in the Era of Change

Abstract: As education is remodelled to online solutions, instructors and students are required to adapt their teaching and learning through different forms of monitoring, regulation and assessment. This remodelling requires conceptual and philosophical reflection relating to stakeholder roles and the relationship between learners and teaching materials within digital learning spaces. With a sample of 276 student participants, this article reports from a Japanese university which shifted all regular face-to-face lecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
2
24
0
2
Order By: Relevance
“…The existence of diverse selves in cyberspace has brought unprecedented challenges to the autonomy development of humans ( Boniel-Nissim et al, 2022 ; Hayes, 2022 ). The diverse self-expression ( Throuvala et al, 2019 ; Duvenage et al, 2020 ), the consistency between online and offline ( Rivers et al, 2021a ; Achterhof et al, 2022 ), the correction of alienated selves ( Coyne et al, 2019 ), and the avoidance of various false selves ( Goke et al, 2021 ; Rivers et al, 2021b ) have become new issues of self-development faced by the adolescents in the Internet era. In this study, the literature on autonomy worldwide was reviewed and compared to further explore adolescents’ autonomy in the context of network culture.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of diverse selves in cyberspace has brought unprecedented challenges to the autonomy development of humans ( Boniel-Nissim et al, 2022 ; Hayes, 2022 ). The diverse self-expression ( Throuvala et al, 2019 ; Duvenage et al, 2020 ), the consistency between online and offline ( Rivers et al, 2021a ; Achterhof et al, 2022 ), the correction of alienated selves ( Coyne et al, 2019 ), and the avoidance of various false selves ( Goke et al, 2021 ; Rivers et al, 2021b ) have become new issues of self-development faced by the adolescents in the Internet era. In this study, the literature on autonomy worldwide was reviewed and compared to further explore adolescents’ autonomy in the context of network culture.…”
Section: Discussionmentioning
confidence: 99%
“…SRL plays a more significant role in online learning environments than in traditional classroom settings. Online contexts tend to demand greater autonomous thinking and action from students due to limited external support [52]. The results of the literature study concluded that SRL plays a positive role in online learning in various educational contexts.…”
Section: Achievement Motivation Srl and Learning Behaviormentioning
confidence: 92%
“…In addition, there are several SRL strategies that have consistently been shown to have a strong influence on achievement, including time management, effort and persistence management, metacognition, and goal setting. Third, motivation and metacognitive processes play an important role in initiating, monitoring, and sustaining self-regulated learning, but their contribution to learning achievement is manifested through action and persistence [52], [53]. In an effort to achieve academic achievement during online learning, both teachers and students need to adapt their teaching and learning.…”
Section: Achievement Motivation Srl and Learning Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recently, some universities in Japan found that their online learning curricula were inadequately designed to address the needs of all students ( Ismailov and Ono, 2021 ). Due to a limited number of published studies in the region ( McEown and Oga-Baldwin, 2019 ; Ismailov and Ono, 2021 ; Rivers et al, 2021 ), this study contributes to the field by providing more evidence on how a UDL-designed course could address inclusion and diversity issues in online learning curricula.…”
Section: Introductionmentioning
confidence: 99%